2015
DOI: 10.5194/isprsannals-ii-2-w2-207-2015
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Annual Average Soil Loss, Based on Rusle Model in Kallar Watershed, Bhavani Basin, Tamil Nadu, India

Abstract: ABSTRACT:Soil erosion is a widespread environmental challenge faced in Kallar watershed nowadays. Erosion is defined as the movement of soil by water and wind, and it occurs in Kallar watershed under a wide range of land uses. Erosion by water can be dramatic during storm events, resulting in wash-outs and gullies. It can also be insidious, occurring as sheet and rill erosion during heavy rains. Most of the soil lost by water erosion is by the processes of sheet and rill erosion. Land degradation and subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…This study found that lack of vegetation cover and type of land use (cultivation and grazing) were the main contributors to the severe and high rate of soil loss in the study area. RUSLE factors can be classified into two categories; environmental and management with the former remaining relatively constant over time while the latter varies considerably [9]. This implies that the management factors affecting both land cover and land use can be manipulated considerably to reduce the rate of the soil loss.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study found that lack of vegetation cover and type of land use (cultivation and grazing) were the main contributors to the severe and high rate of soil loss in the study area. RUSLE factors can be classified into two categories; environmental and management with the former remaining relatively constant over time while the latter varies considerably [9]. This implies that the management factors affecting both land cover and land use can be manipulated considerably to reduce the rate of the soil loss.…”
Section: Discussionmentioning
confidence: 99%
“…Severe erosion prone areas can be delineated and prioritized for erosion mitigation [8]. Effective soil erosion control requires prediction of the amount of soil loss [5] [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thus used to quantify the effect of raindrop and induced runoff on bare soil [Efthimiou, 2014]. It was calculated using the daily rainfall values summarized as monthly and annual rainfall based on similar approaches used or reported by [Efthimiou, 2014;Okorafor, 2017;Rahaman, 2015;Sholagberu, 2016;Ufoegbune, 2011]. A rainfall erosivity index was calculated from the summaries using the modified Fournier index [Essel, 2016] and the resulting values were used to prepare a map.…”
Section: Methodsmentioning
confidence: 99%
“…Cropping in the area is paddy (grain corn). The crop type factor (C) is taken as 0.4 Table - [37] ., …”
Section: The Cover Management Factor (C)mentioning
confidence: 99%